A new neonatal BCG vaccination pathway in England: a mixed methods evaluation of its implementation - Koren Jones; Georgia Chisnall; Tim Crocker-Buque; David Elliman; Jeremy Horwood; Sandra Mounier-Jack; Colin NJ Campbell; Vanessa Saliba; Tracey Chantler (BMC, 2024)
Abstract Introduction The introduction of a national evaluation of newborn screening for Severe Combined Immunodeficiency (SCID) in England triggered a change to the selective Bacillus Calmette-Guerin (BCG) vaccination programme delivery pathway, as this live attenuated vaccine is contraindicated in infants with SCID. The neonatal BCG vaccination programme is a targeted programme for infants at increased risk of tuberculosis and used to be offered shortly after birth. Since September 2021 the BCG vaccine is given to eligible infants within 28 days of birth, when the SCID screening outcome is available. We explore the experiences of those implementing the new pathway, and how they made sense of, engaged with, and appraised the change. Methods A mixed-methods evaluation was conducted between October 2022 and February 2023. This involved national online surveys with BCG commissioners and providers and qualitative semi-structured interviews with commissioners, providers, and Child Health Information System stakeholders in two urban areas. Survey data was analysed using descriptive statistics and interview data was analysed thematically. The data was triangulated using Normalization Process Theory as a guiding framework. Results Survey respondents (n = 65) and qualitative interviewees (n = 16) revealed that making sense of the new pathway was an iterative process. Some expressed a desire for more direction on how to implement the new pathway. The perceived value of the change varied from positive, ambivalent, to concerned. Some felt well-prepared and that improvements to data capture, eligibility screening, and accountably brought by the change were valuable. Others were concerned about the feasibility of the 28-day target, reductions in vaccination coverage, increased resource burden, and the outcome of the SCID evaluation. New collaborations and communities of practice were required to facilitate the change. Three main challenges in implementing the pathway and meeting the 28-day vaccination target were identified: appointment non-attendance; appointment and data systems; and staffing and resourcing. Feedback mechanisms were informal and took place in tandem with implementation. Conclusion The new NHS neonatal BCG service specification has created an effective structure for monitoring and managing the BCG vaccination programme, but further work is required to support delivery of the 28-day vaccination target and improve uptake rates.